Effects of temperature and desiccation on survival rate of haemonchus contortus infective larval stage - P. Iliev; A. Ivanov; P. Prelezov (Trakia Journal of Sciences)
Small ruminants are among the most commonly farmed livestock in Bulgaria. The climate and geographic conditions and pastoral way of growing lead to higher infestation of herds by variety of soil-transmitted helminths. The most spread nematodes are gastro-intestinal strongylids (GIS) causing various diseases of sheep and goats. Abomasal parasite Haemonchus contortus (Nematoda, Trichostrongylidae) constitutes a major part of gastro-intestinal helminthic fauna of small ruminants and is one of the most pathogenic members of this family causing serious economic losses of sheep and goat farms. Pre-parasitic period of H. contortus consisting of segmented eggs, non-infective larvae first and second stage (L1, L2) and infective larvae (L3). This development is also known as exogenous phase and takes place only in environment. Presence of viable and infective L3 on pastures is fully depended on climate conditions, solar radiation, grass and soil type etc. However, temperature and humidity are the most important factors exerting a marked effect on survival of H. contortus L3 on pastures. Resistance of L3 to some atmospheric variables e.g. temperature and humidity could be used to predict occurrence of haemonchosis among small ruminants. The present study aimed to investigate the effect of temperature and desiccation on L3 vitality of H. contortus under laboratory conditions. Experimental infection in lambs by H. contortus was reproduced. Feces were collected after beginning of the patent period of infection. Fecal samples were cultivated for 10 days at 27ºC for developing infective L3 which were then obtained by routine Baermann technique. Acquired L3 were placed under various temperatures (-4ºC; -18ºC; 40ºC; 45ºC; 50ºC) and desiccation. The results clearly showed that L3 were more resistant to desiccation, -4º and 40ºC and less to -18ºC, 45ºC and 50ºC.